Metafora w nazewnictwie roślinnym: polskie i rosyjskie nazwy roślin leczniczych motywowane nazwami ze świata zwierząt - Stec, Wanda (Acta Polono-Ruthenica, 2018)
The paper refers to the use of animal-related metaphor in the linguistic nomination of plants. This phenomenon is illustrated through numerous examples of medicinal plants’ names in Polish and Russian languages, as well as in Latin binomial nomenclature. In the process of plants’ linguistic nomination, it is fairly common to use „zoological” metaphor (metaphor involving animals’ body parts or the connotations associated with the animal given), reflecting the human perception of the world of nature as well as of the interdependence between flora and fauna. Metaphorical names are illustrative and easy to remember. Not only is metaphor a part of plants’ name-formation process, but it may also indicate how the plant is perceived in a society.